Hydrothermal Transformation of Natural Zeolite from Ende-NTT and Its Application as Adsorbent of Cationic Dye - Yulius Dala Ngapa; Sri Sugiarti; Zaenal Abidin (Indonesian Journal of Chemistry, 2016)
A synthetic zeolite was produced from natural zeolite from Ende-Nusa Tenggara Timur (NTT) by hydrothermal method. This study aims to produce synthetic zeolite from Ende natural zeolite to remove cation dye through the adsorption process. Temperature of crystal formation (ageing) was performed at 60 °C for 6 h and hydrothermal process was at 100 °C for 24 h. The natural zeolite produced synthetic NaP1 and synthetic Faujasite. Based on the research results, the synthesis of zeolite by the hydrothermal method can enhance the adsorption capacity and Cation Exchange Capacity (CEC). The adsorption capacity in the natural zeolites of type ZG, ZL and ZC before the hydrothermal process were 17.289, 17.276, and 16.483 mg/g, respectively, and after hydrothermal they increased to 37.398, 37.369 and 37.362 mg/g, respectively. In addition, the CEC increased from 84.154, 81.042, and 77.474 cmol/kg, respectively, to 244.063, 216.354, and 211.432 cmol/kg, respectively. The Langmuir model most closely matched the isothermal adsorption equilibrium process.